Property Rights and Investment Incentives: Theory and Evidence from Ghana - Besley, Timothy (Journal of Political Economy, 1995)
This paper examines the link between property rights and investment incentives. The author develops three theoretical arguments based on security of tenure, using land as collateral and obtaining gains from trade. The paper then presents empirical evidence from two regions in Ghana. The author investigates the possibility that rights are endogenous, with farmers making improvements to enhance their land rights. Finally, he suggests tests for which of the theories might explain the results. Copyright 1995 by University of Chicago Press.